Principles and Methods for the Formation of Sociolinguistic Competence - Kenjayeva Diana Shermatovna; Yayra Abduraimova (International Journal on Human-Computing Studies, 2022)
The modern practice of communication is characterized by the processes of globalization in all areas of human life and activity and leads to an increase in international contacts. At the same time, experience shows that even in cases where the language barrier is overcome, and the interlocutors speak the same language fluently, it is far from always possible to establish understanding. You can pronounce phrases, remarks, exchange information, but understanding in the process of communication may not occur. In this case, there are many reasons and, first of all, it is the lack of socio-cultural competence. Its presence is extremely important, and the very problem of its formation is still being developed in modern methods. The article deals with the issues based on analyzing principles and methods for the formation of sociolinguistic competence.